Evaluation of a novel cationic surfactant based on 2-(2 (dimethylamino)ethoxy)ethanol as a corrosion inhibitor for carbon steel 1018 in 1.0 M HCl solution - A.S. Fouda; S.M. Rashwan; Samy M. Shaban; Hoyeda E. Ibrahim; M.F. Elbhrawy (Egyptian Journal of Petroleum)
Corrosion inhibition of a novel cationic surfactant namely, N-(2-(2-hydroxyethoxy)ethyl)-N,N-dimethyldodecan-1-aminium bromide (HEDDB) was evaluated as a corrosion inhibitor for carbon steel in 1.0 M HCl by electrochemical frequency modulation (EFM), potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and weight loss measurements. Results of Tafel polarization exhibit that the synthesized surfactant HEDDB behaves as mixed-type inhibitor. The effectiveness of temperature on the corrosion rate which evaluated by chemical technique (weight loss) was investigated and assessed. Langmuir’s adsorption isotherm was the preferable fitted isotherm. The results of weight loss clarified that the efficiency of the synthesized surfactant increases with raising both the concentration of the surfactant and the temperature. HEDDB effectiveness on the morphology of metal surface was monitored by Atomic Force Microscopy (AFM) and Scanning Electron Microscope (SEM) techniques. Quantum chemical technique has been employed to discuss the inhibition efficiency by effectiveness of molecular structure of the synthesized inhibitor. The various techniques which used in this research have inhibition efficiency (IE) with the same direction. Keywords: Carbon steel, Cationic surfactant, HCl, HEDDB, Potentiodynamic polarization, EIS, EFM, SEM, AFM